Mental model in learning chemical bonding: a preliminary study - Abd. Halim, Noor Dayana (Elsevier BV, 2013)
Chemical bonding is one of the subjects that involves the use of models, varying from simple ones to sophisticated abstract models possessing considerable mathematical complexity. It is a topic that students commonly find to be problematic, developing a wide range of alternative conceptions. The fact is that students cannot see how the atoms or elementary particles are held together, and how they interact and bond together to form a compound. Student’ misconceptions regarding these chemical bonding concepts begin when they live and operate in a macroscopic world and do not easily follow the shifts between macroscopic and microscopic levels. As a result, they tend to build a non-scientific mental model, which means that the idea is not aligned with scientific concepts. Therefore a preliminary study was conducted in order to investigate students’ mental model in this topic.